2006
DOI: 10.1111/j.1582-4934.2006.tb00431.x
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to tissue engineering of vascularized skeletal muscle

Abstract: Tissue Engineering of skeletal muscle tissue still remains a major challenge. Every neo-tissue construct of clinically relevant dimensions is highly dependent on an intrinsic vascularisation overcoming the limitations of diffusion conditioned survival. Approaches incorporating the arteriovenous-loop model might bring further advances to the generation of vascularised skeletal muscle tissue. In this study 12 syngeneic rats received transplantation of carboxy-fluorescine diacetate-succinimidyl ester (CFDA)-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 21 publications
1
43
1
2
Order By: Relevance
“…The inner volume of 16 cm 3 in our chamber in a cylindrical shape emulates a given volume of tissue that certainly would not be sufficiently nourished by diffusion only, thus approaching clinically relevant dimensions. This is the first study demonstrating de novo formation of axially vascularized connective tissue overcoming the previous limitation to tissue volumes below 1 cm 3 (Bach et al, 2006;Lokmic et al, 2007;Morritt et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The inner volume of 16 cm 3 in our chamber in a cylindrical shape emulates a given volume of tissue that certainly would not be sufficiently nourished by diffusion only, thus approaching clinically relevant dimensions. This is the first study demonstrating de novo formation of axially vascularized connective tissue overcoming the previous limitation to tissue volumes below 1 cm 3 (Bach et al, 2006;Lokmic et al, 2007;Morritt et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…Upon axial vascularization (as shown in this study) and bone tissue formation (as the major aim for future studies, which could imply adding BMPs and/or osteogenic cells, as well as mechanical force stimulation to induce bone formation), the whole de novo-formed bony construct could then be transplanted, in particular including microvascular anastomosis of the AV loop pedicle, into the site of the defect. In previous studies using a rat model, we were able to show that a combination of axial prevascularization of a fibrin matrix using an AV loop and secondary cell injection promotes the survival of injected myoblasts (Bach et al, 2006) and osteoblasts . The inner volume of 16 cm 3 in our chamber in a cylindrical shape emulates a given volume of tissue that certainly would not be sufficiently nourished by diffusion only, thus approaching clinically relevant dimensions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, frequently cell lines are used such as C2C12, which are satellite cells of C3H mice (Dennis et al, 2001;Borschel et al, 2004;Levenberg et al, 2005;Riboldi et al, 2005;Huang et al, 2006a;Boontheekul et al, 2007;Matsumoto et al, 2007). Also, satellite cells harvested from the soleus muscle of rats are used for TE of muscle tissue (Dennis and Kosnik, 2000;Beier et al, 2004;Stern-Straeter et al, 2005;Das et al, 2006;Borschel et al, 2006;Larkin et al, 2006;Bach et al, 2006;Huang et al, 2006b;Boontheekul et al, 2007). Other muscles harvested for TE research include the latissimus dorsi and rectus femoris of rats (Kamelger et al, 2004), the flexor digitorum brevis of rats (De Coppi et al, 2005), the tibialis anterior of rats (Dennis et al, 2001;Huang et al, 2005;Boontheekul et al, 2007), the extensor digitorum longus of mice (Dennis et al, 2001), the human masseter (Lewis et al, 2000;Sinanan et al, 2004;Shah et al, 2005;Stern-Straeter et al, 2008;Brady et al, 2008a) and brachioradialis (Alessandri et al, 2004) and the iliofibularis from female Xenopus laevis frogs (Jaspers et al, 2006) (Table 2).…”
Section: Progenitor Cellsmentioning
confidence: 99%
“…Therefore, the integration of a vascular system is necessary in order to create a functional tissue that is inherently thicker. Pre-vascularized skeletal muscle constructs from cultures of myoblasts, implantation in vivo of muscle constructs, engineered skeletal muscle constructs, and fibrin gel being placed around a preformed ectopic arteriovenous are all techniques that have been tested and proven as successful in rats [88], making it apparent that the previously mentioned cell sheet practice over scaffolds holds a large amount of potential in relation to the concerted vascularization of muscle constructs. It was found that if neovascularization does, in fact, result from this process, new cell sheets can be applied in layers after neovascularization has already occurred on the previous layers of cell sheets [89].…”
Section: Vascularizationmentioning
confidence: 99%